FAKTOR-FAKTOR YANG MEMPENGARUHI FERTILITAS DI KELURAHAN PEKAUMAN KECAMATAN BANJARMASIN SELATAN - Sri Marlina; Ellyn Normelani; Karunia Puji Hastuti (Universitas Lambung Mangkurat, 2017)
The title of this research is the factor that influence fertility in Pekauman, Banjarmasin Selatan this research is arranged by Sri Marlina. The purpose of this research is to know what is the factor that influence fertility in Pekauman, Banjarmasin Selatan. This research use descriptive kuantitative method. The population of this research is the couple og fertile age in Pekauman, Banjarmasin Selatan as much as 539. To obtain the sample responden, the researcher use proporsi area sampling by random sampling or take the random sample that refers to Morgan table, further more the population asa much as 539 after taken sample become 225 (women). The tecknique of data collection based on the primer data and secondary data, namely observation, questionmare, document, reference library. The data that was got done use technique percentage analysis. The result of this research show that there are two factors that influence fertility in Pekauman, Banjarmasin Selatan, namely demografi and non demografi. However, in this research the first factor that influence is factor non demografi. Namely the wife is not work. As much as 63,56% responden mention that the wife is not work.Keyword: Factor, Influence, Fertility